Dinamika Konstitusi Islam: Dari Periode Kekhilafahan hingga Nation-State: Dinamika Konstitusi Islam: Dari Periode Kekhilafahan hingga Nation-State - Sodiqin, Ali; Radiamoda, Anwar M (Institut Agama Islam Negeri (IAIN) Pontianak, 2021)
The debate about the form of the state in Islam took place among Muslim intellectuals. Normatively, the unclear arguments about the relationship between religion and the state in Islamic sources are the leading cause. Historically, there are various forms of Islamic state practiced by Muslims from classical to modern times. This article discusses the dynamics of the constitution practiced by Islamic countries throughout history, from the Prophet to the present. Why is the Islamic constitution different in its arrangement and application in the history of Islamic governance? What are the factors that influence that diversity? The questions discussed in this article use a historical approach to mapping continuity and change in the Islamic constitution. In the period of the caliphate, there was no written constitution as the basis for statehood. The caliph is the constitution itself because of its absolute power. During the nation-state period, there were differences in the placement of Islam as a religious state, shariah as the only source of law, and judicial institutions that sought to adjust the compatibility of the shariah. Four factors cause the diversity of constitution in Islamic countries; the absence of specific rules about state administration in Islamic sources, the centralist and absolute power of caliph, the participation in the development of traditions that developed at that time, and the influence of western countries through colonialism in the Islamic world.